2002
DOI: 10.1029/2001tc001303
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopic evidence for a Pre‐Middle Miocene rain shadow in the western Basin and Range: Implications for the paleotopography of the Sierra Nevada

Abstract: [1] A recently proposed method for approximating the paleorelief of mountain belts makes use of the predictable relationship between the isotopic depletion of precipitation and the net elevation of an orographic barrier over which an air mass rises. This rain shadow effect often creates desert regions on the lee side of mountain belts in which precipitation is isotopically light. Changes in the isotopic composition of precipitation can be estimated from the isotopic composition of authigenic or pedogenic miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
97
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 52 publications
9
97
1
Order By: Relevance
“…During the past decade, numerous isotopic and paleobotanical studies focused on the paleoelevational and climatic history of the western North American Cordillera (e.g., Chase et al, 1998;Wolfe et al, 1998;Poage and Chamberlain, 2002;Horton et al, 2004). In general these two independent approaches arrive at the same interpretation, calling for a spatially and temporally evolving pattern of high elevations from north to south in the Sevier hinterland.…”
Section: Space-time Patterns Of Cordilleran Evolutionmentioning
confidence: 97%
“…During the past decade, numerous isotopic and paleobotanical studies focused on the paleoelevational and climatic history of the western North American Cordillera (e.g., Chase et al, 1998;Wolfe et al, 1998;Poage and Chamberlain, 2002;Horton et al, 2004). In general these two independent approaches arrive at the same interpretation, calling for a spatially and temporally evolving pattern of high elevations from north to south in the Sevier hinterland.…”
Section: Space-time Patterns Of Cordilleran Evolutionmentioning
confidence: 97%
“…Shifting the longitudes of seven of the thick sections of welded ash-flow tuffs mentioned above to compensate for post-Oligocene extension brings the present elevations closer to the extrapolated gradient, but the extrapolated gradient would only intersect the original (Oligocene) longitude of the New Pass Range at about 2.5 km palaeoelevation, which is at least 0.5 km less than what we envisage for the Great Basin Altiplano. A more recent version of the Sierra Nevada uplift history has been derived from palaeoelevations inferred from measurements of oxygen and hydrogen isotopes in Cenozoic authigenic minerals, both within the Auriferous Gravels of the Sierra Nevada and in Miocene and Pliocene basins to the east (Poage and Chamberlain 2002). These workers concluded that nearly all the uplift of the Sierra Nevada occurred between the solidification of the youngest Late Cretaceous batholithic rocks (85 -80 Ma) and the deposition of the Eocene Auriferous Gravels (about 50 -40 Ma).…”
Section: Character Of the Western Margin Of The Altiplanomentioning
confidence: 99%
“…Evidence for these conclusions came from tilted Tertiary sedimentary units on the western flanks of the Sierra Nevada and the development of angular unconformities that suggest post-5-Ma range-wide tilting of a rigid Sierra block resulting in up to 2 km of surface uplift of the Sierra Nevada crest (19). A major phase of Pliocene (Ϸ3-5 Ma) surface uplift contrasts results of stable isotope (15,16), thermochronological (23)(24)(25), cosmogenic nuclide (26), and numerical modeling studies (27) that conclude that the modern orographic barrier of the Sierra Nevada has been a long standing topographic feature of the landscape in the western United States. In summary, these studies conclude that crustal thinning during Basin and Range extension could be held responsible for even an elevation loss since the late Miocene (28) and suggest that a Sierra Nevada rain shadow has been in place since that time (15).…”
mentioning
confidence: 99%
“…1), and the relatively simple atmospheric circulation patterns with moisture sourced in the Pacific ocean and zonal atmospheric flow patterns (12,13). Yet, despite numerous lines of research, the elevation history of the Sierra Nevada is still highly debated, mainly because methods to directly determine paleoaltimetry have only been developed and successfully applied within the last decade (14)(15)(16). On one side, geomorphic studies of tilted strata and associated river incision patterns suggest significant (Ն1.5 km) late Cenozoic (3-5 Ma) surface uplift in the southern and central Sierra Nevada (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%